Perlindungan Hukum Karya Seni Lukisan Yang Di Tiru Dan Disebarluaskan Tanpa Hak - Latupeirissa, Diouf Alexsandro; Pesulima, Theresia Louize; Balik, Agustina (PATTIMURA Law Study Review, 2024)
In Indonesia there are still many copyright violations, one of which is painting. where a painting is imitated and redrawn and sold without the permission of the copyright holder. The research method used is normative juridical using a statutory approach and also a conceptual approach. There are legal sources used including primary legal materials, secondary legal materials, and tertiary legal materials. With the technique of collecting legal materials, it will be linked to legal facts, legal events and legal consequences so that it will be analyzed based on qualitative methods. The results of the research show that legal protection for creators of works of art whose paintings are imitated and distributed without rights is considered a copyright violation. Because it violates the law which involves taking and using it commercially without the permission of the copyright holder. The form of responsibility that must be carried out by the gallery75 owner is to delete the paintings posted on his social media accounts, and make compensation or give a portion of the proceeds obtained.